The Uses Of Ted Talk Video To Improve Students’ Speaking Skill To Eleven Grade Students’ At Sman 5 Samarinda - haya desi afifah danu ado; widi syahtia pane; abdul rohman (Wadah Inovasi Indonesia, 2023)
This research seeks for analyze the effectiveness out of using Ted talks videos to improve students' speaking skills. Thirty-two high school students participated in this study. Data were collected using the Classroom Action Research (CAR) method. In order to achieve aim of this learning, pre-test and post-test were conducted. From extracted data, research found that students' perception of using Ted Talking Videos to improve their public speaking skills was that students responded positively to the author's teaching style. Furthermore, the data indicated that the research used different teaching methods to achieve objective teaching and tried to find strategies based on student needs in different ways. consequently, it was concluded that with the teacher using a tool to support learning to speak, namely Ted talk can help develop students’ speaking skill.